New herpetofaunal records from the Kingdom of Bhutan obtained through citizen science - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2020)
A total of 48 species of amphibians and reptiles from the Kingdom of Bhutan is reported, as a result of citizen science activities.